2013
DOI: 10.1111/pbi.12090
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of cytosolic superoxide dismutase and ascorbate peroxidase leads to salt stress tolerance in transgenic plums

Abstract: These authors have contributed equally to this work.Keywords: antioxidative metabolism, cytosolic ascorbate peroxidase, cytosolic superoxide dismutase, genetic engineering, Prunus domestica, salt stress. SummaryTo fortify the antioxidant capacity of plum plants, genes encoding cytosolic antioxidants ascorbate peroxidase (cytapx) and Cu/Zn-superoxide dismutase (cytsod) were genetically engineered in these plants. Transgenic plum plants expressing the cytsod and/or cytapx genes in cytosol have been generated und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 68 publications
(121 reference statements)
5
77
0
Order By: Relevance
“…These results agreed with those of previous studies (Badawi et al, 2004;Diaz-Vivancos et al, 2013). Saline induced an increase in the ROS level, leading to seed deterioration (Xi et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…These results agreed with those of previous studies (Badawi et al, 2004;Diaz-Vivancos et al, 2013). Saline induced an increase in the ROS level, leading to seed deterioration (Xi et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, all transgenic plum lines had lower levels of H2O2 than non-transformed wild-type plants under salt exposure (100 mM) [211].…”
Section: Ros and Rns Generationmentioning
confidence: 55%
“…Although in planta overexpression of SOD genes often increase endogenous H 2 O 2 levels, such plants are less sensitive to stress-related necrosis if sufficient H 2 O 2 -degradation is conferred by elevated expression of antioxidants like e.g. catalases and peroxidases (Kwon et al, 2002;Tang et al, 2006;Lee et al, 2007;Faize et al, 2011Faize et al, , 2012Diaz-Vivancos et al, 2013). We found that S1 tobacco indeed displays elevated expression of an endogenous glutathione peroxidase (NtGPX) and a tau class glutathione S-transferase (NtGSTU1b), genes that may take part in the degradation of H 2 O 2 and lipid hydroperoxides during oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, transgenic SOD-overexpressing tobacco that is tolerant to necrosis caused by high light intensity and low temperature, also displays elevated levels of endogenous APX (Sen Gupta et al, 1993). Transgenic plants that simultaneously overexpress a SOD and an APX gene show enhanced tolerance to necrosis caused by various abiotic stresses and pathogenic infections (Kwon et al, 2002;Tang et al, 2006;Lee et al, 2007;Faize et al, 2011Faize et al, , 2012Diaz-Vivancos et al, 2013).…”
mentioning
confidence: 99%